SISTEM KERJA PANEL SURYA PORTABLE PADA ALAT ELEKTRONIK RUMAH TANGGA - Masthura Masthura; Mulkan Iskandar Nasution; Dwitha Astari (Universitas Riau, 2023)
The want for electric electricity is an vital a part of human life. Some household appliances use electrical energy from the National Electric Company, but problems often occur in their supply which result in power outages and can disrupt activities and cause harm to the community. The purpose of this research is to understand how to portable solar generators energy can be developed as alternative electrical energy for household electronic devices, to find out how portable solar power generators work as alternative electrical energy for household electronic devices and to find out how solar panels can supplying AC electrified loads to household electronic devices. This research uses an experimental method that innovates in the field of renewable energy by utilizing solar energy (solar panels) as an alternative electrical energy. The test results obtained by this designed tool can turn on household electronic equipment such as rice cookers, fans, LED lights, charge cellphones and laptops with a maximum power of 300 Watts with a time according to the power supplied to the battery capacity so that this hardware maybe used as an alternative electrical energy to replace the generator.